Inside‐and‐Out Semiconductor Engineering for CO2 Photoreduction: From Recent Advances to New Trends. Issue 1 (20th October 2020) - Wang, Shuobo; Han, Xu; Zhang, Yihe; Tian, Na; Ma, Tianyi; Huang, Hongwei
Abstract : Photocatalytic CO2 reduction attracts substantial interests for the production of chemical fuels via solar energy conversion, but the activity, stability, and selectivity of products were severely determined by the efficiencies of light harvesting, charge migration, and surface reactions. Structural engineering is a promising tactic to address the aforementioned crucial factors for boosting CO2 photoreduction. Herein, a timely and comprehensive review focusing on the recent advances in photocatalytic CO2 conversion based on the design strategies over nano‐/microstructure, crystalline and band structure, surface structure and interface structure is provided, which covers both the thermodynamic and kinetic challenges in CO2 photoreduction process. The key parameters essential for tailoring the size, morphology, porosity, bandgap, surface, or interfacial properties of photocatalysts are emphasized toward the efficient and selective conversion of CO2 into valuable chemicals. New trends and strategies in the structural design to meet the demands for prominent CO2 photoreduction activity are also introduced. It is expected to furnish a comprehensive guideline for inside‐and‐out design of state‐of‐the‐art photocatalysts with well‐defined structures for CO2 conversion. Abstract : The advance on CO2 photoreduction based on the design strategies over nano‐/microstructure, crystalline and band structure, surface structure and interface structure for promoting three crucial factors, including light harvesting, charge migration and surface reactions, are systematically summarized. It is expected to furnish a guideline for inside‐and‐out design of photocatalysts with well‐defined structures for CO2 conversion.